2005
DOI: 10.1111/j.1467-2494.2005.00257_2.x
|View full text |Cite
|
Sign up to set email alerts
|

Surfactants, polymers and their nanoparticles for personal care applications

Abstract: A ‘touch me not’ plant folding up rapidly upon being attacked or microbes depositing on teeth or ocean vessels even under hostile conditions are examples in nature that provide inspiration for developing new classes of personal care release or deposition systems. In this paper, development of such systems based on polymer/surfactant colloid chemistry is explored for achieving transport and release of cosmetic and pharmaceutical molecules at desired rates at desired sites. The successful development of products… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 16 publications
0
31
0
1
Order By: Relevance
“…Moreover, mixed-surfactant systems exhibit better surface chemical properties. It has been shown that the nonionic surfactant C 12 E 8 does not adsorb onto solids, but in the presence of an anionic surfactant, synergistic adsorption has been observed [2,3]. Again, nonionic surfactants are known to produce clouding (phase separation) in aqueous solutions at lower temperatures and this separation behavior could be resisted in the presence of ionic surfactants.…”
Section: Introductionmentioning
confidence: 94%
“…Moreover, mixed-surfactant systems exhibit better surface chemical properties. It has been shown that the nonionic surfactant C 12 E 8 does not adsorb onto solids, but in the presence of an anionic surfactant, synergistic adsorption has been observed [2,3]. Again, nonionic surfactants are known to produce clouding (phase separation) in aqueous solutions at lower temperatures and this separation behavior could be resisted in the presence of ionic surfactants.…”
Section: Introductionmentioning
confidence: 94%
“…En effet, la taille nanométrique de ces structures entraîne une augmentation de la proportion des atomes présents à leur surface, pouvant conduire à une plus grande réactivité de surface, une résistance élevée et des propriétés électriques modifiées. Les applications technologiques sont nombreuses, notamment dans les secteurs industriels innovants, tels que l'industrie cosmétique (écrans solaires, rouges à lèvres, pâtes dentifrices…) [1,2], l'industrie automobile (peintures, pneumatiques, lubrifiants, pare-brise…) [3,4], le secteur de la santé (pharmacocinétique et biodisponibilité des médicaments, matériels prothétiques, imagerie moléculaire…) [5,6].…”
unclassified
“…Nanogels of polyacrylamide and polyacrylic acid have been created and shown to be capable of encapsulating molecules [56]. These have been suggested to offer the slow release of fragrances and the potential for improved release of active ingredients such as antidandruff agents, etc.…”
Section: Nanochemistry Nanoparticles and Hair Care Cosmeticsmentioning
confidence: 99%